(untitled) (Economics and region, 2018)
The article looks at the problems which agricultural and road building machine-building faces today. Our industry has the necessity of carrying out such works. Plants would use this situation. In fact, situation is different. Our manufactures has lower quality and lose in competition with foreign manufactures. Ukrainian consumer prefer foreign machines, though some kinds of domestic produce are still in demand. Our economists should study the problems mentioned, and scientists should improve the machines’ designs.The expectations for the foreign investors who will come and bring new technologies and technics as well as raise Ukrainian production are not well-grounded. After the crisis of 2008 the developed nations understood that the advanced economics which can survive periodic crises without significant losses is economically developed economics with working industrial enterprises. Ukrainian business must finance research to increase our machine quality. We see serious works by Ukrainian scientists who can give adequate results. The authors are convinced that activation of innovative activity will allow to improve its positions.